Five-Year Reoperation Rates of 2-Level Lumbar Total Disk Replacement Versus Fusion: Results of a Prospective, Randomized Clinical Trial. Issue 1 (February 2018) - Radcliff, Kris; Spivak, Jeffrey; Darden, Bruce; Janssen, Michael; Bernard, Thierry; Zigler, Jack
Abstract : Study Design: Long-term analysis of prospective randomized clinical trial data. Summary of Background Data: Lumbar total disk replacement (TDR) has been found to have equivalent or superior clinical outcomes compared with fusion and decreased radiographic incidence of adjacent level degeneration in single-level cases. Objective: The purpose of this particular analysis was to determine the incidence and risk factors for secondary surgery in patients treated with TDR or circumferential fusion at 2 contiguous levels of the lumbar spine. Methods: A total of 229 patients were treated and randomized to receive either TDR or circumferential fusion to treat degenerative disk disease at 2 contiguous levels between L3 and S1 (TDR, n=161; fusion, n=68). Results: Overall, at final 5-year follow-up, 9.6% of subjects underwent a secondary surgery in this study. The overall rate of adjacent segment disease was 3.5% (8/229). At 5 years, the percentage of subjects undergoing secondary surgeries was significantly lower in the TDR group versus fusion (5.6% vs. 19.1%, P =0.0027). Most secondary surgeries (65%, 17/26) occurred at the index levels. Index level secondary surgeries were most common in the fusion cohort (16.2%, 11/68 subjects) versus TDR (3.1%, 5/161 subjects, P =0.0009). There no statistically significant difference in the adjacent level reoperation rate between TDR (2.5%, 4/161) and fusion (5.9%, 4/68). The most common reason for index levels reoperation was instrumentation removal (n=9). Excluding the instrumentation removals, there was not a significant difference between the treatments in index level reoperations or in reoperations overall. Conclusions: There were significantly fewer reoperations in TDR patients compared with fusion patients. However, most of the secondary surgeries were instrumentation removal in the fusion cohort. Discounting the instrumentation removals, there was no significant difference in reoperations between TDR and fusion. These results are indicative that lumbar TDR is noninferior to fusion.